PENGARUH PENDIDIKAN KESEHATAN TERHADAP MINAT WUS UNTUK MELAKUKAN PEMERIKSAAN IVA DI PUSKESMAS BAKUNASE. - Lede Vanesa (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2018)
The incidence numbers of cervical cancer increased each year. One way to earlydetect is to do an IVA (visual inspection of acetic acid). The phenomenon that occurs in society today is still low interest to perform IVA which causes detectable cervical cancer already at an advanced stage. Identify interest women of childbearing age before and after health education in intervention group and control group and to analyze the effect of health education on WUS interest to conduct IVA inspection. This research is a quasy experiment research with purposive sampling technique with a sample of 72 respondents. Data analysis used T-test statistic. Based on the results of statistical tests used T-test obtained p value of 0.000 is smaller than the value of α (0.05). This means that there is Influence of Health Education to WUS Interests to Conduct IVA Inspection in the working area of ​​Bakunase Health Center. The advice given is for women of childbearing age (WUS) in the working area of ​​Bakunase Health Center to realize the interest by conducting IVA inspection. Keywords: Health Education, Interests, IVA